Conceiving Mary's Agency: Towards a Barthian Mariology - De Stigter, Christopher Paul (2023)
This essay argues for the possibility of a ‘Barthian’ Mariology particularly through an analysis of human agency. I first show that Karl Barth's articulation of Mary in I/2 of the Church Dogmatics marginalizes Mary's agency in part due to his anti-Roman Catholic polemic and his gender binary. I then correct Barth with Barth by showing how his mature Christology advances an account of human agency commensurate with Mariology. With this Christological account of human agency established, I construct a genuinely ‘Barthian’ Mariology that shows her as the eschatological and prototypical human agent.